South Africa and the Case for Renegotiating the Peace - Pierre du, Toit (AFRICAN SUN MeDIA, 2016)
South Africa is awash with policy failures, and policy confusion. We argue firstly, that our current discord over policy details has its origin in the (celebrated) negotiated transition. We hold that the vote count of an 85% majority in the Constituent Assembly in 1996 obscured the reality that the Constitution meant different things to different negotiators. The result was that South Africa, from the very start of the democratic era, lacked a national consensus on how to go about consolidating democracy. We keep on failing to build a proper roof over our democracy because the constitutional foundations are weak. In this book, we present a way out for South Africa from its persistent policy failures and policy confusion. We argue that in order to do so the major stakeholders in South Africa will have to jointly renegotiate the meaning of the Constitution. It is not a call for a new CODESA. CODESA was a conference to establish a new democracy. This is a call for a process to salvage that very democracy, where stakeholders will have to clarify what the pillars of the 1996 Constitution are: what does it stand for, what does it represent, what does it embody, and what kind of future does it authorise South Africans to try to construct.